The Impact of Electronic Technology for Maps and Graphs in the Collection of Geographical Material With the Second Grade Students Average and Their Motivation to Learn - Kazem Al-Azzawi, Mohammed Jawad; Abdul-Saheb, Iqbal Mutasher (Opción, 2019)
The impact of geographical material with the second grade students average and their motivation to learn, The sample of the research consisted of (98) students divided into three groups respectively, the first experimental group (34), and the second experimental group (31) Student, and the control group (33) student, the researchers adopted the experimental approach, As for the research tools, the test is composed of (36) a paragraph of multiple choice, the researchers used the following statistical methods in analyzing the results of the research (Analysis of variance, and Sheffeh test), The results showed the following: First: The first and second experimental group is superior to the control group. Second, the first and second experimental groups outweigh the control group in a driving measure towards learning.